Art in the making - Fischer, Chris 1950-; Svenningsen, Jesper (Statens Museum for Kunst, 2018)
"How does a work of art come into being? How is the idea for it born? What processes does the work go through before it reaches its final form? What does the working process tell us about the finished result? These are among the many related questions to which this book tries to supply answers. We follow the artists' work from the first stage, when the initial hazy idea is set down on paper, to the emergence of a fully finished work of art. The study includes over 200 sketches, graphic works, paintings and sculptures by some of the most outstanding names in western art, ranging over the period from c. 1460 to 1950. Both the processes as well as the works that result from them are subjected to keen analysis. So are the social conditions that have contributed to the making of art--including education, commissioning, social expectations, tradition, influences from the works of others and the organization of the artists' workshop."--From the back cover